Sequential procurement with limited commitment - Nicolas Fugger; Vitali Gretschko; Martin Pollrich (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We analyze the problem of a buyer who chooses a supplier for a long-term relationship via an auction. The buyer lacks commitment to not renegotiate the terms of the contract in the long run. Thus, suppliers are cautious about the information revealed during the auction. We show theoretically and experimentally that first-price auctions perform poorly in terms of efficiency and buyer surplus. Suppliers may pool on a high bid to conceal information. Second-price auctions retain their efficient equilibrium and generate substantial surplus for the buyer. We demonstrate that optimal mechanisms require concealing the winning bid with a strictly positive probability.
Keywords: 330